THE POSITIVE AND NEGATIVE EXPERIENCE SCALE ADAPTATION FOR TURKISH UNIVERSITY STUDENTS - Bulent Baki Telef (European Scientific Journal, ESJ, 2015)
The purpose of this study is to examine the psychometric properties of the Scale of Positive and Negative Experience, which was developed to measure the positive and negative affects, in the Turkish culture. Study group of the research consists of 401 university students, 280 (70%) of which were female and 121 (30%) were male. Results of the exploratory factor analysis support the two-factor structure as in the original scale. Results of the confirmatory factor analysis show that fit indexes are at acceptable levels. As a result of the convergent validity study, significant relationships were discovered between the Scale of Positive and Negative Experience and Positive-Negative Affect Scale, Satisfaction with Life Scale and Life Orientation Test. It can be said by taking the Cronbach alpha coefficient and the test-retest results into account that the test has high reliability. The findings obtained as a result of the research were discussed through comparison with the results of the scale adaptation conducted in different cultures.